Biochemical and Molecular Aspects of Phosphorus Limitation in Diatoms and Their Relationship with Biomolecule Accumulation - José Pablo Lovio-Fragoso; Damaristelma de Jesús-Campos; José Antonio López-Elías; Luis Ángel Medina-Juárez; Diana Fimbres-Olivarría; Corina Hayano-Kanashiro (Biology, 2021)
Diatoms are the most abundant group of phytoplankton, and their success lies in their significant adaptation ability to stress conditions, such as nutrient limitation. Phosphorus (P) is a key nutrient involved in the transfer of energy and the synthesis of several cellular components. Molecular and biochemical mechanisms related to how diatoms cope with P deficiency are not clear, and research into this has been limited to a few species. Among the molecular responses that have been reported in diatoms cultured under P deficient conditions is the upregulation of genes encoding enzymes related to the transport, assimilation, remobilization and recycling of this nutrient. Regarding biochemical responses, due to the reduction of the requirements for carbon structures for the synthesis of proteins and phospholipids, more CO2 is fixed than is consumed by the Calvin cycle. To deal with this excess, diatoms redirect the carbon flow toward the synthesis of storage compounds such as triacylglycerides and carbohydrates, which are excreted as extracellular polymeric substances. This review aimed to gather all current knowledge regarding the biochemical and molecular mechanisms of diatoms related to managing P deficiency in order to provide a wider insight into and understanding of their responses, as well as the metabolic pathways affected by the limitation of this nutrient.